تقييم أداء مشاريع التعاون الدولي في سورية وفقاً لمعايير OECD-DAC: تطبيق على برنامج التحديث والتطوير الصناعي (IMUP-Syria ) - الجزائرلي معاذ; بلال رغداء (Latakia University Journal - Economic and Legal Sciences Series, 2018)
The purpose of this study is to explore the extent to which the five evaluation criteria adopted by the Development Assistance Committee at the Organization for Economic Cooperation and Development (effectiveness, relevance, efficiency, impact, and sustainability) are applied to international cooperation projects in Syria. This study addresses the overall performance of the Industrial Modernization and Upgrading Programme (IMUP Syria) that had been implemented in Syria (Ministry of Industry) during the period 2007-2013 (in two phases). The study is based on a questionnaire that was distributed to 32 respondents of those who are involved in implementing the programme: beneficiaries and other stakeholders who are working in the ministry; either affecting or affected by the programme outputs. The study concludes that the overall level of the success of the programme is estimated around above average, and that the levels of effectiveness, relevance, efficiency, impact, and sustainability of the programme are all above average as well. It also demonstrates that there are no significant differences in responses among different subgroups of respondents (gender, education, experience, and occupation) with respect to each of the dimensions of performance covered in the study. The recommendations of this study include: Evaluating the programme periodically in order to ensure fulfilling the actual desired outcomes, promoting the adoption of the five criteria in evaluation, monitoring and follow-up in order to ensure the success of projects and their sustainability, and, finally, considering the replication of this study to other ongoing projects. تهدف هذه الدراسة إلى التعرف على مدى تطبيق معايير التقييم الخمسة (الفاعلية، الارتباط، الكفاءة، الأثر، الاستدامة) المعتمدة من قبل لجنة المساعدة الإنمائية التابعة لمنظمة التعاون الاقتصادي والتنمية على برنامج التحديث والتطوير الصناعي (IMUP-Syria) الذي يعد نموذجاً لمشاريع التعاون الدولي في سورية. تم إجراء الدراسة على الأداء العام لبرنامج التحديث والتطوير الصناعيIMUP الذي نُفذ في الجمهورية العربية السورية ممثلة بوزارة الصناعة خلال الفترة 2007-2013 (على مرحلتين)، وذلك من خلال توزيع استبانة على 32 مبحوثاً من المعنيين بتنفيذ البرنامج من مستفيدين وأطراف مصالح آخرين من العاملين في الوزارة سواءً مؤثرين أو متأثرين بمخرجات البرنامج. أظهرت نتائج الدراسة أن مستوى نجاح البرنامج وفقاً للتقييمات يفوق المتوسط ككل ويفوق المتوسط كذلك بحسب كافة المعايير الدولية المعتمدة وهي الفاعلية والارتباط والكفاءة والأثر والاستدامة. كما أظهرت نتائج الدراسة أنه لا توجد فروق ذات دلالة معنوية بين متوسط إجابات المبحوثين حسب متغيرات الجنس والمؤهل العلمي وسنوات الخبرة وذلك من أجل كافة محاور الاستبانة (المعايير الخمسة للتقييم) باستثناء متغير الصفة الوظيفية حيث جاءت الفروق دالة إحصائياً لكافة محاور الاستبانة. وخلصت الدراسة إلى مجموعة من التوصيات أهمها: ضرورة إجراء تقييم دوري للبرنامج يعكس مدى تحقيق النتائج المرجوة على أرض الواقع، وتعزيز اعتماد المعايير الخمسة في عمليات التقييم والرقابة والمتابعة بغرض إنجاح هذه المشروعات وضمان استدامتها، وأخيراً، النظر في تطبيق ذات الدراسة على مشروعات أخرى قائمة.